A modified percutaneous transforaminal endoscopic surgery for central calcified thoracic disc herniation at the T11/T12 level using foraminoplasty and decompression: A case report - Lisheng, Hou; Suhuai, Tian; Dong, Zhang; Qing, Zhou (Frontiers in Surgery, 2023)
Background: Thoracic disc herniation (TDH) is uncommon. Central calcified TDH (CCTDH) is even rare. Traditional open surgery was a golden standard way performed to treat CCTDH but with high risk of complications. Recently, percutaneous transforaminal endoscopic decompression (PTED) is adopted to treat TDH. Gu et al designed a simplified PTED technique named percutaneous transforaminal endoscopic surgery ( PTES) to treat various types of lumbar disc herniation with advantages of simple orientation, easy puncture, reduced steps, and little X-ray exposure. However, PTES has not been reported to treat CCTDH in literature. Methods: We described one CCTDH case treated with modified PTES through unilateral posterolateral approach under local anesthesia and conscious sedation with the help of a flexible power diamond drill. Results: A 50-year-old male with progressive gait disturbance and bilateral leg rigidity with paresis and numbness was diagnosed with CCTDH at T11/T12 level based on MRI and following CT examinations. Modified PTES was performed on November 22, 2019. The foraminoplasty process was divided into initial fluoroscopic and final endoscopic stage. At fluoroscopic stage, the hand trephine’s saw teeth were just rotated into the lateral portion of ventral bone from superior articular process (SAP) to seize the SAP firmly; while at endoscopic stage, to remove the ventral bone from SAP safely under direct endoscopic visualization. During endoscopic decompression process, the soft disc fragments ventral to the calcified shell was undermined to form a cavity using an inside-out technique. Then a curved dissector or a flexible radiofrequency probe was used to dissect the thin bony shell from the dura sac. Eventually, the shell was fractured within the cavity piece by piece to remove the whole CCTDH and achieve satisfied decompression. Blood loss was little. No complication was found. The symptoms were gradually alleviated and almost completely recovered at 3-month follow-up. The mJOA score improved to 17 at 3months’ follow-up and 18 at two years’ follow-up compared to that of 12 points preoperatively. Conclusions: Modified PTES may be an alternative minimally invasive technique for the treatment of CCTDH and provide similar or better outcomes over traditional open surgery.